Understanding conflict resolution - Wallensteen, Peter (Thousand Oaks : SAGE Publications Ltd, 2023)
"Understanding Conflict Resolution, the updated sixth edition, is a contemporary, applied, and critical Conflict Resolution textbook designed as the perfect guide for students studying Security and Peace and Conflict studies. With an emphasis on peace agreements between and with states and this book relies on data provided by the well-known Uppsala Conflict Data Program (UCDP), which Wallensteen founded and now has become a standard source for systematic information on conflicts, wars and peace"--
Includes bibliographical references and index.
Keywords: conflict resolution